Light transport in quasi-one-dimensional disordered waveguides composed of locally two-dimensional random square lattices. Issue 12 (4th July 2017) - Xu, Yuchen; Zhang, Hao; Lin, Yujun; Zhu, Heyuan
Abstract: We present numerical studies on the light transport properties which are tuned by the disorder strength in quasi-one-dimensional disordered waveguides consisting of periodically arranged scatterers with random dielectric constant. The transport mean free path is found to be inversely proportional to the square of the relative fluctuation of the dielectric constant as in the 1D and 2D cases but the proportionality coefficient is between those of 1D and 2D. The transport properties of light through a sample with a fixed size can be tuned from ballistic to localized regime as well, and a generalized scaling function is introduced to determine the light transport status in such a sample. The calculation of the energy density profile of the most transmitted eigenchannel clearly exhibits the transition of transport behaviour from diffusion to localization.